Hubungan Antara Status Ekonomi Dengan Minat Ibu Terhadap Kontrasepsi Tubektomi Di Bpm Ny. Istianah Ernawati Desa Ketapang Tanggulangin Sidoarjo: The Relationship Between Economic Status and Mother's Interest in Tubectomy Contraception at Bpm Ny. Istianah Ernawati Ketapang Village Tanggulangin Sidoarjo - Umaroh, Muflikhatul; Frisky, Elga Mia (Jurnal Kebidanan Midwiferia, 2018)
According the first research in BPM by Mrs. Istianah Ernawati, Amd Keb Ketapang village Tanggulangin-Sidoarjo through the deployment of quotioner, obtained result from 10 respondents there are 2 (20%) respondents with high economic status, 1 (10%) respondent was very interested to use family planning tubektomi, 1 (10%) respondent was interested to use family planning tubektomi. Respondents with average economic status, 2 (20%) respondents, 1 (10%) who was very interested, 1 (10%) who was interested to use family planning Tubektomi. Respondents with under economic status, 6 (60%) respondents, 1 (10%) respondent was interested to use family planning tubektomi, 5 (50%) respondents wasn’t interested to use family planning tubektomi. From research result there are still mary mothers with low economic status who were not interested to tubektomi contraception, it happened because economic status. Analitical research design by cross sectional. Population and sample in research is all mothers who have more than 2 children and mothers age which are more than 35 years old who came to BPM Mrs. Istianah Ernawati, Amd.Keb Ketapang village Tanggulangin-Sidoarjo with the total is 32 respondents. Instrument research used check-list. Data analyzing proccess used Korelasi Spearman Test. The result of Korelasi Spearman Test be obtained rs calculating 0,516 > rs table 0,362 that H0 is refused and H1 is accepted, so there is positive contact between economic status with mothers interest to tubektomi contraception in BPM Mrs. Istianah Ernawati, Amd.Keb Ketapang village Tanggulangin-Sidoarjo in 2015. So more and high economic status mothers and high interested mothers tubektomi contraception.